Isolation and Identification of Antibiotic Resistance Genes in Multi-Drug Resistance Escherichia coli Isolates from With Urinary Tract Infections - Oudah , Marwah Ali; Aziz, Nidda F.; Obaid, Bushra Hamad (American Journal of Biology and Natural Sciences, 2026)
Escherichia coli is an intestinal bacterium that frequently causes UTIs and nosocomial infections. Resistance of E. coli to various antibiotics has been widely reported, making treatment difficult for UTI patients. The purpose of this study is to determine the sensitivity of E. coli in the urine of UTI patients to ciprofloxacin antibiotics. Bacterial samples were obtained from the isolation of patients suffering from UTI using Endo's agar medium selective media, the growing E. coli was then subjected to a sensitivity test at a temperature of 37oC for 24 hours to observe and measure the inhibition zone formed. This research was a descriptive laboratory study with a completely randomized design, data were analysed using the Kruskal-Walli’s test and continued with post hoc. The study results showed that the incidence of UTI was highest in women (60%), while in men it was 40%. Most of the isolates had fluoroquinolone resistance determining genes located on the chromosome and , while resistance genes located on the plasmid were found in 5 isolates, (n=1), (n=2) and (n=2). Although the frequency of PMQR genes, including qnr, oqxA, and oqxB, was low in 21MDR ciprofloxacin-resistant E. coli isolates, their existence may allow for horizontal gene transfer among other Enterobacteriaceae bacteria and aid in the selection of resistant mutants following ciprofloxacin exposure. It is highly likely that the presence of a ciprofloxacin resistance gene, either on the plasmid or chromosome, is what causes the MDR ciprofloxacin resistance pattern in E. coli isolates.